2014
DOI: 10.5539/ass.v10n8p123
|View full text |Cite
|
Sign up to set email alerts
|

Parental Attachment, Inter-Parental Conflict and Late Adolescent’s Self-Efficacy

Abstract: The main purpose of this study was to determine the relationship between parental attachment, inter-parental conflict and self-efficacy among 374 college students aged 17 to 19 years old in Iran. The probability proportional to size sampling technique was used to obtain sample size. The Inventory of Parent and Peer Attachment, the Children's Perception of Inter-parental Conflict Scale, and the General Self-Efficacy Scale were used to measure parental attachment, inter-parental conflict and self-efficacy, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 60 publications
1
11
1
Order By: Relevance
“…Children who have a better attachment with their parents during infancy are more likely to have successful social and emotional development, in particular, learning how to regulate their feelings. 27,28 Using valid and reliable research tools showed that BF mothers were less likely to have perceived severity of illness for their child and more likely to have confidence to perform medical care compared to NBF mothers. Therefore, to promote breastfeeding, Table1: Factor analysis and reliability of the scales used.…”
Section: Discussionmentioning
confidence: 98%
“…Children who have a better attachment with their parents during infancy are more likely to have successful social and emotional development, in particular, learning how to regulate their feelings. 27,28 Using valid and reliable research tools showed that BF mothers were less likely to have perceived severity of illness for their child and more likely to have confidence to perform medical care compared to NBF mothers. Therefore, to promote breastfeeding, Table1: Factor analysis and reliability of the scales used.…”
Section: Discussionmentioning
confidence: 98%
“…Various studies have shown that KMC has had favorable results for neonates and mothers, which includes: favorable effects on heart rate, oxygen saturation and respiratory rate [ 8 ], maintaining body temperature and sleeping of the infant [ 9 ], positive effect on mental and cognitive development, better performance in physical tests during early childhood [ 10 ], helping to increase mother's emotional feelings toward the newborn [ 11 , 12 ], positive effect on family attachment [ 13 , 14 ], and confidence in mother-child care [ 15 ]. It may also affect the subsequent outcomes and long-term welfare of the mothers and their babies for reducing risky behaviors later in her life [ 16 ]. Since there has been no research on the effect of KMC on the physiological indices of premature infants in Hamadan province, this study investigated the effect of KMC on the physiological parameters such as heart rate, respiratory rate, arterial oxygen saturation and body temperature in premature neonates admitted in NICU of Fatemiyeh Hospital, Hamadan city, Iran.…”
Section: Introductionmentioning
confidence: 99%
“…However, some research has found no difference when investigating mother-adolescent and father-adolescent attachment and the devel opment of internalizing symptoms (De Minzi, 2006;Papini et al, 1991). Many studies have found motheradolescent attachment security to be higher than fatheradolescent attachment security, which may explain the mixed findings in regard to fatheradolescent attachment security and the development of internalizing symptoms (Devi et al, 2017;Hellenthal, 2006;Parsa, Yaacob, Redzuan, Parsa, & Esmaeili, 2014). Overall, stud ies of parent-adolescent attachment have shown that insecure attachments may lead to specific adjustment outcomes, including the development of internalizing symptoms (Agerup et al, 2014;Brumariu & Kerns, 2010).…”
Section: Discussionmentioning
confidence: 99%